Chlorine Concentration and Phytoplankton Diversity in the Streams around Tondano Watershed, North Sulawesi, Indonesia - Wantasen, S.; Luntungan, J. N.; Koneri, R. (Jurnal Pendidikan IPA Indonesia, 2022)
The use of chlorine in agriculture and settlements increases and impacts surrounding waters, such as watersheds:  The land area is a unit with rivers and tributaries that function to accommodate, store and distribute water from rainfall to the sea naturally.  The environmental condition of the Tondano watershed is important to study in terms of chlorine distribution, considering that residential and agricultural activities in the watershed can cause residues in the aquatic environment, which harm the environment, especially phytoplankton. This study aims to examine the concentration of chlorine and its impact on the phytoplankton diversity in the Tondano watershed, North Sulawesi, Indonesia. Using the composite method, water quality sampling to calculate chlorine concentration was carried out at 17 river locations using the composite method, while six river stations represented phytoplankton sampling. Chlorine concentration was measured using UV-VIS spectrophotometry, while plankton sampling used a plankton net with a mesh size of 40 µm and a net mouth diameter of 20 cm. The results show that the highest chlorine concentration was found in Tondano Hilir River (0.05 mg/L), followed by the Kakas River downstream (0.04 mg/L). Chlorine concentration distribution in other rivers has the same concentration (0.03 mg/L).  Quality standard Chlorine according to Government Regulation number 22/2021 Appendix VI Class II is 0,03 mg/L. The highest number of species and index of phytoplankton species diversity was found in the Hulu Panasen River, while the highest species abundance was found in the Tondano River downstream. The correlation analysis of species diversity index with chlorine concentration did not show a significant relationship with the diversity of phytoplankton, but aquatic ecosystems have experienced moderate ecological pressure.